DEVELOPMENT OF INFORMATION TECHNOLOGY STRATEGIC PLANNING FOR MANUFACTURING INDUSTRY (CASE STUDY: PT MCM) - Hardjo, Leonardus; Suharjito, Suharjito (Bina Nusantara University, 2013)
IT Department in PT MCM has to carry out the duties and functions of developing solution to support the business unit in their operation and gain some benefits which should be obtained by using IT in manufacturing such as increasing efficiency, improving the effectivity in making decision and helping to promote the products. This study aims to design information technology strategic planning in accordance with the strategic plan. The research method is using the IT Strategic Planning framework of Alex Cullen and Marc Cecere. This study uses SWOT and IT Balanced Scorecard to analyze the needs of IT at PT MCM. The results of this study are recommended strategic steps to optimize the implementation of IT in the company to improve the performance from IT division to obtain the benefits by implementing IT in manufacturing and to form IT Blueprint, which is part of the information technology strategic plan in PT MCM.